An efficient method for conjugation of a lipopolysaccharide from Salmonella enterica sv. Minnesota with probes bearing hydrazine or amino functional groups - Pallarola, Diego Andres (2008)
A conjugation method for coupling probes bearing hydrazine or primary amino groups to a lipopolysaccharide (LPS) is described. LPS is modified through the hydroxyl groups present in its O-antigen moiety by activation with cyanogen bromide in aqueous acetone using triethylamine to enhance the electrophilicity of CNBr. The method yields conjugates with good labeling ratios, preserving the endotoxic activity of the lipid A moiety, which in blood exerts pleiotropic effects on many tissues and organs, resulting in multiple-organ damage, circulatory collapse, and death. Conjugation of smooth-form LPS from Salmonella enterica sv. Minnesota to dansyl hydrazine yielded a labeling ratio of 330 nmol dansyl/mg LPS, with nearly no loss of the original endotoxic activity. In the case of horseradish peroxidase, in which a spacer was introduced, the ratio was 28 nmol HRP/mg of LPS, preserving 65% of the original endotoxic activity. This work shows that under these conditions of CNBr activation, the labeling process has practically no effect on the endotoxic behavior of LPS. The method can be used effectively for the conjugation of LPS to probes bearing primary amino, hydrazine, or hydrazide functional groups.